Effect of Character Education to Entrepreneurial Readiness For Vocational High School (VHS) Students (Indonesian Journal of Learning Education and Counseling, 2019)
The research objective is to determine the effect of character education on entrepreneurship readiness of Vocational High School students. research needs to be held. This research was conducted through a literature review of references and relevant research results, and continued through focus group discussion (FGD). The research found: (1) there is an influence of character education on the level of entrepreneurial readiness of vocational students; (2) character education values that influence entrepreneurial readiness, are creative, independent, honest, cooperative, curiosity, disciplined, courageous to take risks, strong motivation for success, communicative, realistic, commitment, never give up, oriented to action, leadership, and innovation; (3)Vocational students must obtain character education in accordance with the character possessed by an entrepreneur. Because in character education includes discipline, honesty, cooperation, curiosity, creativity and independence, almost all must also be owned by an entrepreneur; (4) The relationship between vocational students who already have character education will grow a mentality for entrepreneurship; andEntrepreneurial readiness is influenced by four dimensions of entrepreneurial readiness, namely intention, ability, learning and attraction; and (5)In order for entrepreneurial readiness to be realized optimally, there must be support from the government, changes in various theories that lead to improvement, and open to various developing innovations.